Effect of thermal and non-thermal processing on antioxidant potential of cowpea seeds. Issue 1 (1st January 2018) - Yadav, Neelam; Kaur, Devinder; Malaviya, Ritika; Singh, Monika; Fatima, Mahrukh; Singh, Lovy
ABSTRACT: Legumes are a good source of bioactive components, besides being nutrient dense. These components have antioxidant properties and have a protective role against free radicals. Legumes like cowpeas are usually consumed after certain processing, so the present study was intended to assess antioxidant property of selected four cultivars of cowpea after going through various thermal (autoclaving, microwave, boiling, and roasting) and non-thermal (soaking and fermentation) processings. Thermal processing reduced total phenolic content (TPC), total flavonoid content (TFC), and ferric reducing antioxidant power (FRAP) in all cultivars with respect to antioxidant activity of raw cultivars, while DPPH scavenging activity increased after all thermal treatments excluding few thermal processings. Non-thermal processing revealed increase in TPC, DPPH scavenging activity, and FRAP values, while TFC content showed a decreasing trend. A moderately high correlation between TPC and DPPH scavenging activity was observed in both kinds of thermal treatments indicating the role of phenolic compounds for antioxidant activity. It was concluded from the study that fermentation processing has promising effects on retention and enhancement of antioxidant activity of cowpea cultivars.